Hydrogels - Haider, Sajjad; Haider, Adnan (IntechOpen, 2018)
This new important book is a collection of research and review articles from different parts of the world discussing the dynamic and vibrant field of hydrogels. The articles are linking new findings and critically reviewing the fundamental concepts and principles that are making the base for innovation. Each chapter discusses the potential of hydrogels in diverse areas. These areas include tissue engineering, implants, controlled drug release, and oil reserve treatment. The book is offering an up-to-date knowledge of hydrogels to experienced as well as new researchers.